Bleach / Fire Fallow - Charise, Andrea (Ars Medica, 2020)
strange resonances of intergenerational connection. "Bleach" is an autobiographical reflection that explores the strange resonances of intergenerational connection. The author considers how the memory of her grandmother—and the transmitted stories of her grandmother’s own childhood—can be seen anew through her own apprehension of growing old. “As I nurse my own hair’s / whitening, I coax age through / and out of me—my body, in time, entangling / these hard traces of the past.” Integrating images of bleaching and stains, farming and public health, depression and growth, "Bleach" braids together past and present in its search for “lessons / on how to grow old.” In “Fire Fallow,” the author draws on the conventions of prose poetry to explore the phenomenological nature of mental health and illness, burnout especially. Using the historical catastrophe of the volcanic eruption of Pompeii as a conceit, "Fire Fallow" explores the terrible paradoxical intimacies of creation and destruction, the chronic fiction of a work-life balance. Turning away from false comforts–the insufficient language of resilience, regrowth, and regarging–this poem grapples with the reality of health care work and life with a clear-eyed lesson: "What lights our way will burn our skin and scorch the earth."